ANALISIS BREAK EVEN POINT (BEP) PADA INDUSTRI PERCETAKAN (DIGITAL PRINTING) DI KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Teguh Nopriadi Putra; Lapeti Sari; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conductedin on printing industry (digital printing) in Kecamatan Tembilahan Kabupaten Indragiri Hilir. Analysis of the break even point is a situation where the company does not suffer losses also didn't get the profit. Commonly, this analysis gives information about margin of safety to the management of how much the decrease of the selling can be reckoned so that the company will not having a loss.The purpose of this research is to know the amount and value of sales which must be achieved at the point of BEP, the margin of safety of the sale and obstacles encountered. The analysis method used is descriptive quantitative dan qualitative.quantitative analysis wa conducted by using formula break even point (BEP) ang margin of safety than discussed with qualitative methods on the obstacles faced.According to the research result, the level of BEP that is accomplished by printing industy (digital printing) in Kecamatan Tembilahan Kabupaten Indragiri Hilir is 327,43 m2 (Rp.9.823.034,237). Margin of safety printing industry (digital printing) worked with the level of safety is 70,89 %. It can be concluded that the decrease of the organic fertilizer selling could not be more than 70,89 % (Rp.23.925.375) from the planning. Printing industry (digital printing) in Kecamatan Tembilahan Kabupaten Indragiri Hilir has successfully produced above the BEP value. Aside from that, there are some obstacles such as damage to the machine, digital printing technology, , bad debts, availability of raw materials from the other region and frequent power outagesKeywords : break even point, margin of safety, obstacles in printing industry (digital printing)